The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.17576/mjas-2016-2005-16
|View full text |Cite
|
Sign up to set email alerts
|

Zeta Potential and Environmental Scanning Electron Microscopy Analysis in Deproteinisation of Natural Rubber Latex

Abstract: This paper describes the effect of protein denaturants namely, urea and sodium dodecyl sulphate (SDS) in the deproteinisation of high ammonia natural rubber latex (HA-NRL). It had been shown that latex proteins were reduced more in the presence of urea alone (48%) than in the presence of SDS (18%). The synergistic effect when both urea and SDS were used in the latex deproteinisation attributed to the higher protein removal efficacy (55%). Higher zeta potential value was observed when only SDS was used, suggest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 18 publications
1
1
0
Order By: Relevance
“…On the other hand, Ariyawiriyanan [ 56 ] suggests that the zeta potential has an incidence on the particle sizes of the DPNR, finding that at lower zeta potentials the particle size decreases. Therefore, it is inferred that possibly the smallest particle sizes were obtained from the system PEG6000 L. The zeta potential of Colombian NRFL shows similar values as reports of other countries [ 44 , 59 , 60 ].…”
Section: Resultssupporting
confidence: 75%
“…On the other hand, Ariyawiriyanan [ 56 ] suggests that the zeta potential has an incidence on the particle sizes of the DPNR, finding that at lower zeta potentials the particle size decreases. Therefore, it is inferred that possibly the smallest particle sizes were obtained from the system PEG6000 L. The zeta potential of Colombian NRFL shows similar values as reports of other countries [ 44 , 59 , 60 ].…”
Section: Resultssupporting
confidence: 75%
“…This could be explained by the phospholipids, carbohydrates, proteins and other non-rubber ingredients contributing charge species to HANRL, resulting in significant negative zeta potential values. 36 The highest negative zeta potential for the HANRL with 30 phr zinc thiolate showed that the colloidal particles were stabilised, which thus inhibited particle aggregation, unlike with lower zeta potential values. Moreover, the presence of potassium oleate acted as a colloid stabiliser, preventing rubber particle coalescence in the controlled sample.…”
Section: Resultsmentioning
confidence: 95%